2000
DOI: 10.1046/j.1365-2249.2000.01298.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative roles of free fatty acids with reactive nitrogen intermediates and reactive oxygen intermediates in expression of the anti-microbial activity of macrophages againstMycobacterium tuberculosis

Abstract: SUMMARYWe assessed the role of free fatty acids (FFA) in the expression of the activity of macrophages against Mycobacterium tuberculosis in relation to the roles of two major anti-microbial effectors, reactive nitrogen intermediates (RNI) and reactive oxygen intermediates (ROI). Intracellular growth of M. tuberculosis residing inside macrophages was accelerated by treatments of macrophages with either quinacrine (phospholipase A 2 (PLA 2 ) inhibitor), arachidonyl trifuloromethylketone (type IV cytosolic PLA 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 41 publications
1
43
0
1
Order By: Relevance
“…Chem., 9 (5): 260-268, 2015 C o n t r o l There are several stimuli were reported to activate the immune system, especially to induce cytokines and NO (Gharavi et al, 2011). Nitrogen oxide has complex and diverse functions in physiological and pathophysiological phenomena; accumulated evidence suggests that NO and oxygen radicals such as superoxide are key molecules in the pathogenesis of various infectious diseases (Akaki et al, 2000). Studies have shown that severe cases of malaria are accompanied by increased iNOS activity and the subsequent production of NO (Bryk et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Chem., 9 (5): 260-268, 2015 C o n t r o l There are several stimuli were reported to activate the immune system, especially to induce cytokines and NO (Gharavi et al, 2011). Nitrogen oxide has complex and diverse functions in physiological and pathophysiological phenomena; accumulated evidence suggests that NO and oxygen radicals such as superoxide are key molecules in the pathogenesis of various infectious diseases (Akaki et al, 2000). Studies have shown that severe cases of malaria are accompanied by increased iNOS activity and the subsequent production of NO (Bryk et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Peningkatan aktivitas makrofag dalam sekresi ROI yang mencapai puncaknya pada minggu kedua setelah infeksi, juga didukung dengan hasil penelitian berikutnya yang menunjukkan bahwa pada minggu kedua setelah infeksi selain aktivitas sekresi ROI yang mencapai puncak, aktivitas makrofag dalam fagositosis juga mencapai puncaknya pada waktu yang sama (24). Reactive oxygen intermediate merupakan produk oksidatif makrofag yang memainkan peranan penting dalam mekanisme pembunuhan M. tuberculosis, yang aktivitasnya diinduksi oleh sitokin IFN-γ dan TNF-α (25,26). Kemampuan BCG dalam menstimulasi respon imun seluler khususnya dalam mekanisme sebagai efektor oksidatif pada mencit telah banyak dilaporkan.…”
Section: Diskusiunclassified
“…[3] In this situation, produced peroxynitrite (ONOO-) and other reactive nitrogen and oxygen intermediates plays an important role in host defense against the invading bacteria. [4,5] Consequently, many bacterial pathogens have evolved protective mechanisms against reactive oxygen and nitrogen intermediates. [6] On the other hand, it has been cleared that mutation in the catalase-peroxidase katG gene of M. tuberculosis resulted in resistance to isoniazid [7] and mutation in the ß avoprotein mono-oxygenase etaA gene, resulted in resistance to ethionamide.…”
Section: Introductionmentioning
confidence: 99%